Case reportsOstial stenosis of the left main coronary artery as the result of the previous percutaneous coronary intervention on the left coronary artery - Mencel, Grzegorz; Kowalczyk, Jacek; Swierad, Marcin; Swiatkowski, Andrzej; Honisz, Grzegorz; Kalarus, Zbigniew; Sredniawa, Beata (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
A 76-year-old patient was admitted to hospital due to recurrent chest pain. Angiography revealed multivessel coronary artery disease with significant stenosis in medial and distal parts of the left main coronary artery (LMCA). Two drug-eluting stents (DES) were implanted from the medial part of the LMCA to the proximal part of the left anterior descending (LAD) artery. An excellent angiographic result was achieved. After 20 days the patient returned to our clinic because of acute coronary syndrome (ACS). Angiography showed 80% stenosis in the ostial LMCA. The lesion was stented with DES, obtaining a good angiographic result.